STRATEGI PENGEMBANGAN GEREJA PERKOTAAN BERBASIS KELOMPOK SEL - Yansen, Jusry; Marbun, Purim (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
Urban communities that are busy with various activities or work and also dense traffic often make most of the congregation in a dilemma. The basic needs of humans as creatures that require interaction are lost. Sunday worship is unable to provide solutions to these basic needs. Cell groups are a church development strategy that can be a driver of church growth. Cell groups are fellowships between fellow believers in a group of people who are driven by the spirit of caring for each other. From this life of caring for each other, cell groups become the most anticipated fellowship because in it there is togetherness in love, praying for each other, and growing together in the truth of God's word. This study was conducted using a descriptive qualitative approach with a literature study method and limited observation. The results of this study indicate that there is a correlative relationship between the implementation of cell groups and church development.